2020
DOI: 10.1111/dmcn.14533
|View full text |Cite
|
Sign up to set email alerts
|

Profile of hospital admissions for adults with cerebral palsy: a retrospective cohort study

Abstract: Aim To retrospectively profile acute hospital admissions for a defined cohort of adults with cerebral palsy (CP). Method Five years of health service data were interrogated to identify acute health service use by adults with CP. Admission types were described, admission reasons categorized using International Classification of Diseases, 10th Revision codes, and length of stay (LOS) calculated. Any differences between paediatric and adult subsets were explored. Results Individuals with CP constituted 2922 admis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 22 publications
4
18
0
Order By: Relevance
“…The high rate of respiratory presentations is consistent with previous literature on respiratory risk factors in those with CP, alongside published studies on inpatient hospital admissions in this cohort 12,18,22 . Study results also showed an increase in rates of pneumonia between paediatric and adult cohorts.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The high rate of respiratory presentations is consistent with previous literature on respiratory risk factors in those with CP, alongside published studies on inpatient hospital admissions in this cohort 12,18,22 . Study results also showed an increase in rates of pneumonia between paediatric and adult cohorts.…”
Section: Discussionsupporting
confidence: 90%
“…The high rates of age‐related comorbidities and health exacerbations in those with CP could contribute to the high hospital admission rate seen in the adult subgroup (71%) 3 . This positive age‐related trend is consistent with previous analysis of inpatient admissions of adults with CP at Monash Health 18 . A similar trend is seen in the general population, and in international studies on people with CP 5,12,22 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Regardless the general consensus stands that people with CP have worse physical health than the general population. For example, people with CP are at increased risk of developing diabetes, heart disease, and stroke (Peterson et al, 2015), and have higher rates of hospital admissions and access acute inpatient services for emergency health care more than people without CP (Morgan et al, 2020). People with CP have an increased risk of early mortality due to ischaemic heart disease, cerebrovascular disease, respiratory diseases, and circulatory disorders (Ryan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%